Role of FK506-sensitive signals in asthmatic lung inflammation - Tomiaki, Chihiro; Miyauchi, Kosuke; Ki, Sewon; Suzuki, Yoshie; Suzuki, Narumi; Morimoto, Hiroshi; Mukoyama, Yohei; Kubo, Masato (Frontiers in Immunology, 2022)
Asthma is airway inflammatory diseases caused by the activation of group 2 innate lymphoid cells (ILC2s) and type 2 helper T (TH2) cells. Cysteine proteases allergen cause tissue damage to airway epithelial cells and activate ILC2-mediated type 2 airway inflammation. FK506 is an immunosuppressive agent against calcium-dependent NFAT activation that is also effective against asthmatic inflammation. However, the effects of FK506 on cysteine protease allergen-mediated airway inflammation remain unclear. In this study, we investigated the suppressive effects of FK506 on airway inflammation. FK506 had a partial inhibitory effect on ILC2-dependent eosinophil inflammation and a robust inhibitory effect on T cell-dependent eosinophil inflammation in a cysteine protease-induced mouse asthma model. The infiltration of T1/ST2+ CD4 T cells in the lungs contributed to the persistence of eosinophil infiltration in the airway; FK506 completely inhibited the infiltration of T1/ST2+ CD4 T cells. In the initial phase, FK506 treatment targeted lung ILC2 activation induced by leukotriene B4 (LTB4)-mediated calcium signaling, but not IL-33 signaling. FK506 also inhibited the IL-13-dependent accumulation of T1/ST2+ CD4 T cells in the lungs of the later responses. These results indicated that FK506 potently suppressed airway inflammation by targeting ILC2 activation and T1/ST2+ CD4 T cell accumulation.